2014
DOI: 10.1016/j.cct.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Exercise for methamphetamine dependence: Rationale, design, and methodology

Abstract: Background Effective pharmacotherapies to treat methamphetamine (MA) dependence have not been identified, and behavioral therapies are marginally effective. Based on behavioral studies demonstrating the potential efficacy of aerobic exercise for improving depressive symptoms, anxiety, cognitive deficits, and substance use outcomes, the study described here is examining exercise as a potential treatment for MA-dependent individuals. Methods This study is randomizing 150 participants with MA dependence at a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This point may be critical because several exercise trials are being conducted for addiction treatment in humans, but most introduce exercise well after the initiation of abstinence. 42 Our findings showing that exercise beginning during early abstinence effectively reduces cocaine seeking are consistent with our previous work and recent work by others. For example, several studies have demonstrated an acute beneficial effect of exercise at reducing cocaine seeking when exercise immediately precedes or is concurrent with reinstatement testing.…”
Section: Discussionsupporting
confidence: 93%
“…This point may be critical because several exercise trials are being conducted for addiction treatment in humans, but most introduce exercise well after the initiation of abstinence. 42 Our findings showing that exercise beginning during early abstinence effectively reduces cocaine seeking are consistent with our previous work and recent work by others. For example, several studies have demonstrated an acute beneficial effect of exercise at reducing cocaine seeking when exercise immediately precedes or is concurrent with reinstatement testing.…”
Section: Discussionsupporting
confidence: 93%
“…Inclusion criteria were MA dependence, English proficiency, age 18 to either 45 years for men or 55 years for women (per American College of Sports Medicine [ACSM, 2000] guidelines for supervision of exercise by non-physicians), and the ability to attend exercise or health education sessions. Individuals were excluded if they exhibited medical impairment that compromised their safety as a participant, met criteria for opiate dependence, or had a psychiatric impairment that warranted hospitalization or primary treatment (see Mooney et al, 2014, for further details on the study design).…”
Section: Methodsmentioning
confidence: 99%
“…For a detailed description of study procedures, see Mooney et al, 2013. Inclusion criteria were MA dependence per DSM-IV, age 18–45 years for men and age 18–55 years for women (per American College of Sports Medicine [ACSM, 2000] guidelines for supervision of exercise with non-physicians), vital sign stability, and ability to comply with study procedures.…”
Section: Methodsmentioning
confidence: 99%